Assessing the efficacy of two modes of digital learning object package on students’ achievement and interest in rocket and satellite in post covid’19 era - Ogundeji, Oluwatomisin Marvellous (Education and Development Research, 2024)
This paper examines the efficacy of two modes of digital learning object package on students’ achievement and interest in rocket and satellite in post covid’19 Era. The study adopted Quasi-Experimental research design. A sample of 132 SS3 physics students selected using purposive sampling technique. The instruments used for data collection were Rocket and Satellite Achievement Test (RSAT) and Students Interest Questionnaire (SIQ) developed by the researchers. The reliability coefficient indices of 0.88 and 0.83 for RSAT and SIQ were obtained using Kuder-Richardson 20 (KR-20) formula and Cronbach Alpha. The data obtained were analyzed using mean and standard deviation to answer the research questions and analysis of covariance (ANCOVA) to test the Null hypotheses. Findings revealed that DLO with tutor-led instructional model significantly promotes students’ achievement and interest in rocket and satellite compared to DLO self-paced instructional model. Gender had some influence on physics students’ achievement and interest in Rocket and Satellite but not statistically significant. Based on the findings it was recommended amongst others that: Physics teachers should adopt the use of DLO with Online teaching packages (especially using, tutor-led instructional model) to enhance students’ achievement and interest in the Rocket and Satellite.